WORKING CAPITAL MANAGEMENT AND PERFORMANCE OF AGRICULTURAL COOPERATIVE SOCIETIES IN IMO STATE, NIGERIA. (Nigerian Journal of Cooperative Economics and Management, 2023)
The study examines working -capital management and performance of agricultural cooperative societies in Imo State, Nigeria. The study was motivated by the need to determine the influence of working capital management on cooperative performance. The specificobjectives are to: ascertain the extent to which accounts receivables influences cooperative members return on Investment (ROI) in Imo State and determine the extent to which accounts payable influence cooperative members return on Investment (ROI) in Imo State.The area of study is Imo State where samples of 139 cooperatives were selected from the population of 213 registered cooperatives in the study area. The instrument used for data collection was questionnaire. The study employed regression technique, one sample T-test, mean, frequency and percentage in analyzing the data obtained. The study found out that the P-value of 0.031 is less than the alpha value 0.05 and is found to be significant. It was also found that account receivables affect cooperative profitability and size of dividend and welfare package. It was also revealed that accounts payable on cooperative performance ensures delivery of orders, increases credit worthiness, brings about sustainable stakeholder relations and increases inventory size.The study therefore recommends that proper management of various components of working capital need to be maintained to ensure adequate amountof working capital and liquidity. In order to successfully run the cooperative that control measures need to be taken on stock so as to help in preventing stock outs and also help in decision making in the procurement function. Proper training need to be organized by the cooperatives to ensure that the executives are well trained to execute working capital management practices which will in turn lead to improvement in the profitability of operations, managerial efficiency, minimize financial risk and ensure liquidity.
Keywords: Working capital management; performance; agricultural cooperative; return on investment